Peran Public Relations Membangun Image Pariwisata Bali dalam Erupsi Gunung Agung - I Gusti Ayu Ratna Pramesti Dasih (UHN IGB Sugriwa Denpasar, 2018)
Public Relations play a role in the policy order by using two-way communication to support the success of the policy by explaining, informing, maintaining or promoting it to the public so as to create public opinion. Public Relations targets are audiences who have certain communication needs to develop messages that are desired so that they can be communicated. The interaction process of Public Relations aims to create public opinion as an input that is beneficial for both parties. Efforts to instill understanding, fosterpublic motivation and participation, to gain trust and mutual benefit so as to get a good image of the public.